Evaluasi Sistem Pengendalian Internal Atas Pengelolaan Aset Tetap Daerah Pada BPKAD Kabupaten Kupang - Queeni Leylani Rimafanda Mozes; Moni W. Muskanan, Indah Mutiara (Jurnal Mirai Management, 2025)
This study aims to evaluate the internal control system over the management of regional fixed assets at the Regional Financial and Asset Management Agency (BPKAD) of Kupang Regency. The management of regional fixed assets plays a crucial role in achieving effective, efficient, transparent, and accountable governance. However, several issues remain, such as irregular asset administration, uncertified assets, and weak supervision and reporting. This research employs a descriptive qualitative approach, with data collected through in-depth interviews and document studies. Data analysis was conducted using the five components of the Government Internal Control System (SPIP) as regulated in Government Regulation No. 60 of 2008, namely the control environment, risk assessment, control activities, information and communication, and monitoring. The results indicate that the implementation of the internal control system at BPKAD Kupang Regency has been fairly good but not yet optimal, especially in the aspects of risk assessment and monitoring. The study also found the need to improve human resource capacity, update asset information systems, and consistently enforce supervision procedures. Therefore, this evaluation is expected to serve as a basis for BPKAD Kupang Regency to strengthen its internal control system and enhance accountability in managing regional fixed assets. Keywords: Internal Control System, Fixed Asset Management, SPIP, BPKAD Kupang Regency